2011
DOI: 10.1111/j.1600-0404.2011.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported symptoms in patients on antiepileptic drugs in monotherapy

Abstract: Our unblinded observational study of self-reported symptoms suggested LTG was overall the drug with the least self-reported symptoms. Larger studies are needed to determine whether this was a truly significant difference. LEV had a different side effect profile to older AED. Confounding factors were depression and uncontrolled epilepsy. This observation should be further tested with randomized studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
1
15
1
1
Order By: Relevance
“…The mood complaints of patients using LEV treatment were an essential factor in our study and are in line with a number of studies and meta-analyses [27][28][29][30]. LEV had an adverse event profile within the range of the other older drugs like PHT but with a different profile; self-reported anger and hostility were particularly frequent [13,15].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mood complaints of patients using LEV treatment were an essential factor in our study and are in line with a number of studies and meta-analyses [27][28][29][30]. LEV had an adverse event profile within the range of the other older drugs like PHT but with a different profile; self-reported anger and hostility were particularly frequent [13,15].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the newer anti-epileptic drug LEV is known for its high-risk to cause mood effects [12,13]. Mood side-effects are therefore most common in patients-reports with (LEV) [14,15]. The subjective reports about these drugs seem to be by and large equivalent to measured cognitive effects of these AEDs [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous small study using the LAEP we also found a disturbingly high prevalence of self-reported adverse effects suggesting that the burden of taking AED is perhaps much higher than that widely assumed by doctors. 9 This study also showed that even in monotherapy LEV was overall not better tolerated than older AED but had a different adverse effect profile. Feelings of anger were reported as always occurring in 33% of patients on LEV as opposed to 19% on sodium valproate, 16% on carbamazepine and 15% LTG, in keeping with our current study (9).…”
Section: Discussionmentioning
confidence: 71%
“…To achieve this, we focused on the large subgroup of patients with AED monotherapy allowing for an in-depth analysis of specific predictors down to the level of distinct AEDs. Previous studies including patients receiving AED monotherapy treatment for either new-onset epilepsy [5], controlled epilepsy [11], or epilepsy of different degrees of severity [10] did not report differences of individual AEDs in regard to overall or specific AE burden. This finding was confirmed by the current total study population and by the subset of the current monotherapy patients.…”
Section: Discussionmentioning
confidence: 96%
“…Due to potentially additive or even supra-additive pharmacodynamic effects in polytherapy regimen [9], possible AED-specific AEs can only be assessed in patients treated with AED monotherapy. Studies on patients treated with monotherapy have not yet able to demonstrate any such differences on AE occurrence between commonly administered AEDs [5,10,11]. In these studies, however, the respective number of patients treated with individual AEDs was supposedly too small to detect clear-cut effects.…”
Section: Introductionmentioning
confidence: 97%